A Multimodal Text Analysis of K-Pop Fans Representation on Indonesia Film Television - Ranny Rastati (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2022)
K-Pop has become a global phenomenon that affects Indonesian pop culture. K-Pop contributes various inspirations for Indonesian pop culture products, including television shows. In January 2021, Indonesian film television (FTV) entitled Bagaimana Menyadarkan Istriku yang Terlalu Terobsesi K-Pop (How to Remind My K-Pop-Obsessed Wife) went viral on social media. The FTV received criticism for its depiction of K-Pop fans which was considered excessive and incorrect. The study examines how Indonesian-made FTV represents K-Pop fans in the FTV. The research was conducted with multimodal text analysis. The scene that includes K-Pop fan activity was selected based on the five levels of fan activities by Henry Jenkins. Those scenes indicated four fan activities: modes of reception, critical and interpretive practice, consumer activism, and alternative social community. The scenes were then analyzed by seeing the relation between visual (image) and audio (dialog) modes using the relation between modes by Bogucki. The analysis showed some inaccuracies in K-Pop fan activities, such as the use of K-Pop terms, pronunciation, merchandise, fashion, and hairstyle, were found. The FTV storyline focused on affairs and marriage issues. K-Pop was merely used to attract audience interest and to reach more viewers. K-Pop telah menjadi fenomena global yang mempengaruhi budaya pop Indonesia. K-Pop menyumbangkan berbagai inspirasi untuk produk budaya pop Indonesia, termasuk acara televisi. Pada Januari 2021, film televisi Indonesia (FTV) berjudul Bagaimana Menyadarkan Istriku yang Terlalu Terobsesi K-Pop menjadi viral di media sosial. FTV tersebut menuai kritik karena dinilai berlebihan dan tidak tepat dalam menggambarkan sosok penggemar K-Pop. Penelitian ini bertujuan untuk mengkaji bagaimana FTV buatan Indonesia merepresentasikan penggemar K-Pop di FTV tersebut. Penelitian dilakukan dengan analisis teks multimodal. Adegan yang mencakup aktivitas penggemar K-Pop dipilih berdasarkan lima tingkat aktivitas penggemar oleh Henry Jenkins. Adegan-adegan tersebut menunjukkan empat aktivitas penggemar: mode penerimaan, praktik kritis dan interpretatif, aktivisme konsumen, dan komunitas sosial alternatif. Adegan kemudian dianalisis dengan melihat hubungan antara mode visual (gambar) dan audio (dialog) menggunakan hubungan antar mode oleh Bogucki. Hasil analisis menemukan beberapa ketidakakuratan dalam aktivitas penggemar K-Pop, seperti penggunaan istilah K-Pop, pengucapan, merchandise, fesyen, dan gaya rambut. Jalan cerita FTV ini berfokus pada perselingkuhan dan masalah pernikahan. Isu K-Pop hanya digunakan untuk menarik minat penonton dan menjangkau lebih banyak penonton.